Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1037/dev0001311
|View full text |Cite
|
Sign up to set email alerts
|

Chinese mothers’ parental burnout and adolescents’ internalizing and externalizing problems: The mediating role of maternal hostility.

Abstract: Parental burnout is a state that parents feel exhausted in their parental role. Although past research has examined concurrent correlates of parental burnout, the impacts of parental burnout on adolescent development over time remain largely unknown. The current study explored the indirect mechanisms linking mothers' parental burnout to adolescents' later internalizing and externalizing problems through maternal hostility among Chinese families. Using a sample of 606 adolescents (51.5% boys; M age = 12.89 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 71 publications
(105 reference statements)
6
36
0
Order By: Relevance
“…This study found that parental psychological aggression plays a mediating role between parental burnout and adolescents’ problem behavior. This finding is consistent with previous studies that found that parental burnout leads to a range of negative parenting behaviors, such as reduced warmth and support for children [ 3 ], increased neglect and violence [ 4 ], hostility [ 12 ], aggression [ 18 ], and increased negative treatment of children, such as denial and rejection [ 4 ]. This study shows that parental burnout can also increase parents’ psychological aggression toward adolescents.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study found that parental psychological aggression plays a mediating role between parental burnout and adolescents’ problem behavior. This finding is consistent with previous studies that found that parental burnout leads to a range of negative parenting behaviors, such as reduced warmth and support for children [ 3 ], increased neglect and violence [ 4 ], hostility [ 12 ], aggression [ 18 ], and increased negative treatment of children, such as denial and rejection [ 4 ]. This study shows that parental burnout can also increase parents’ psychological aggression toward adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…Children are the subjects of parenting behavior, and burned-out parents’ parenting behavior ultimately affects the healthy development of their children. However, only a few studies have examined the direct effects of parental burnout on children’s development [ 12 ]. Therefore, based on family system theory, this study used paired data to build a moderated mediation model to explore the influence and underlying mechanism of parental burnout on adolescents’ problem behavior.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations